Taboo Words Expressed in Get Hard Movie - Zulfahmi Irwan; Noer Jihad Saleh; Abidin Pammu; Achmad Taqlidul Chair Fachruddin (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This research discussed about translating cultural taboo words Get Hard movie. The aim of this research is to explain the translation strategies of taboo words. This research focused on Batistella’s theory about types of taboo words that are Epithet, Profanity, Vulgarity, and Obscenity, and Karjalainen’s theory about motives of using taboo words that are Psychological motive, Linguistic motive and Social motive. This research applied descriptive qualitative method in revealing data. In collecting the data, the rsearcher used note taking as instrument in order to get the valid data. As the result of the research, it was found there were four types of taboo words and three motives of using taboo words in Get Hard movie. The most common types and motives of using taboo words in Get Hard movie is Epithets and Psychological motive.